Membrane Formation in Liquids by Adding an Antagonistic Salt - Sadakane, Koichiro; Seto, Hideki (Frontiers in Physics, 2018)
Antagonistic salts are composed of hydrophilic and hydrophobic ions. In a binary mixture, such as water and organic solvent, these ion pairs preferentially dissolve to those phases, respectively, and there is a coupling between the charge density and the composition. The heterogeneous distribution of ions forms a large electric double layer at the interface between these solvents. This reduces the interfacial tension between water and organic solvent, and stabilizes an ordered structure, such as a membrane. These phenomena have been extensively studied from both theoretical and experimental point of view. In addition, the numerical simulations can reproduce such ordered structures.